FERMI LARGE AREA TELESCOPE DETECTION OF PULSED gamma-RAYS FROM THE VELA-LIKE PULSARS PSR J1048-5832 AND PSR J2229+6114 - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Axelsson, Magnus; Baldini, Luca; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; et al. (Astrophysical Journal, 2009)
We report the detection of gamma-ray pulsations (>= 0.1GeV) from PSR J2229+ 6114 and PSR J1048-5832, the latter having been detected as a low-significance pulsar by EGRET. Data in the gamma-ray band were acquired by the Large Area Telescope (LAT) aboard the Fermi Gamma-ray Space Telescope, while the radio rotational ephemerides used to fold the gamma-ray light curves were obtained using the Green Bank Telescope, the Lovell telescope at Jodrell Bank, and the Parkes Telescope. The two young radio pulsars, located within the error circles of the previously unidentified EGRET sources 3EG J1048-5840 and 3EG J2227+6122, present spin-down characteristics similar to the Vela pulsar. PSR J1048-5832 shows two sharp peaks at phases 0.15 +/- 0.01 and 0.57 +/- 0.01 relative to the radio pulse confirming the EGRET light curve, while PSR J2229+ 6114 presents a very broad peak at phase 0.49 +/- 0.01. The gamma-ray spectra above 0.1 GeV of both pulsars are fit with power laws having exponential cutoffs near 3 GeV, leading to integral photon fluxes of (2.19 +/- 0.22 +/- 0.32) x 10(-7) cm(-2) s(-1) for PSR J1048-5832 and (3.77 +/- 0.22 +/- 0.44) x 10(-7) cm(-2) s(-1) for PSR J2229+6114. The first uncertainty is statistical and the second is systematic. PSR J1048-5832 is one of the two LAT sources whichwere entangled together as 3EG J1048-5840. These detections add to the growing number of young gamma-ray pulsars that make up the dominant population of GeV gamma-ray sources in the Galactic plane.
CRIS-Team WoS Importer:2020-01-15